Accumulation of HIV-1 drug resistance after continued virological failure on first-line ART in adults and children in sub-Saharan Africa - Boender, T; Kityo, C; Boerma, R; Hamers, R; Ondoa, P; Wellington, M; Siwale, M; Nankya, I; Kaudha, E; Akanmu, A; Botes, M; Steegen, K; et al. (Oxford University Press, 2016)
Objectives Limited availability of viral load (VL) monitoring in HIV treatment programmes in sub-Saharan Africa can delay switching to second-line ART, leading to the accumulation of drug resistance mutations (DRMs). The objective of this study was to evaluate the accumulation of resistance to reverse transcriptase inhibitors after continued virological failure on first-line ART, among adults and children in sub-Saharan Africa. Methods HIV-1-positive adults and children on an NNRTI-based first-line ART were included. Retrospective VL and, if VL ≥1000 copies/mL, pol genotypic testing was performed. Among participants with continued virological failure (≥2 VL ≥1000 copies/mL), drug resistance was evaluated. Results At first virological failure, DRM(s) were detected in 87% of participants: K103N (38.7%), G190A (21.8%), Y181C (20.2%), V106M (8.4%), K101E (8.4%), any E138 (7.6%) and V108I (7.6%) associated with NNRTIs, and M184V (69.7%), any thymidine analogue mutation (9.2%), K65R (5.9%) and K70R (5.0%) associated with NRTIs. New DRMs accumulated with an average rate of 1.45 (SD 2.07) DRM per year; 0.62 (SD 1.11) NNRTI DRMs and 0.84 (SD 1.38) NRTI DRMs per year, respectively. The predicted susceptibility declined significantly after continued virological failure for all reverse transcriptase inhibitors (all P < 0.001). Acquired drug resistance patterns were similar in adults and children. Conclusions Patterns of drug resistance after virological failure on first-line ART are similar in adults and children in sub-Saharan Africa. Improved VL monitoring to prevent accumulation of mutations, and new drug classes to construct fully active regimens, are required.